Designing and developing an Intelligent Chatbot for Product Inquiry Analysis in E-Stores Using NLP and LLMS Models - Aymen, Gasmi; Supervisor: Said, Gadri (Mohamed Boudiaf University of M'sila, 2025)
E-commerce is undergoing a paradigm shift thanks to the integration of artificial intelligence technologies, particularly intelligent chatbots, which enhance user experience and provide im mediate and efficient customer support. This research presents the development of a multilin gual chatbot, based on Retrieval Augmented Generation (RAG) technology and Large Language Models (LLMs), to provide accurate and contextual answers in Arabic, French, and English. The system contributes to reducing the burden on human support teams and increasing customer sat isfaction, with the ability to dynamically update the knowledge base. The model demonstrates high adaptability, making it applicable to multiple fields beyond e-commerce.